2012
DOI: 10.1177/1533317512467679
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Cost of Care in Patients With Alzheimer’s Disease

Abstract: Disparities in cost among minority-to-minority populations were just as prevalent, if not higher, than minority-white disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
5
42
2
Order By: Relevance
“…Interestingly, Gilligan and colleagues (2013) found significant differences between minorities and whites and among minority groups in Medicaid payments for health costs among patient admissions with AD. [47] Moreover, our findings support potential racial disparities in hospitalization characteristics among AD patient admissions, which may explain the racial disparities observed in care costs. However, future research is needed to further investigate other socio-demographic factors that may explain why these differences are occurring.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, Gilligan and colleagues (2013) found significant differences between minorities and whites and among minority groups in Medicaid payments for health costs among patient admissions with AD. [47] Moreover, our findings support potential racial disparities in hospitalization characteristics among AD patient admissions, which may explain the racial disparities observed in care costs. However, future research is needed to further investigate other socio-demographic factors that may explain why these differences are occurring.…”
Section: Discussionsupporting
confidence: 71%
“…Gilligan et al analyzed cost of care in Medicaid patient populations and found that among individuals who received 1 unique AD medication, total health care expenditures decreased significantly compared to those receiving no pharmacotherapy (p < 0.001); however, when level of exposure increased to 2 or more drugs, there was no difference in cost between individuals who received medication therapy as compared to those who received none [28]. A systematic review conducted by Cappell et al examining pharmacoeconomic studies of these medications also suggests that cost of care is lower when AD patients receive pharmacotherapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Medicaid beneficiaries with a diagnosis of Alzheimer's dementia that included both Medicaid and Medicare claims data, researchers found significant differences in the costs of care by race/ethnicity 576 . These results demonstrated that black/African Americans had significantly higher costs of care than whites or Hispanics/Latinos, primarily due to more inpatient care and more comorbidities.…”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%